2019
DOI: 10.1177/0734242x18819752
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking performance of solid waste management and recycling systems in East Africa: Comparing Kigali Rwanda with other major cities

Abstract: This paper aims to benchmark performance of combined solid waste management (SWM) and recycling systems in major cities of East Africa. The Wasteaware indicators are used to present a detailed systems analysis for Kigali in Rwanda, including a mass flow diagram; comparative data are taken from the Wasteaware database for Dar es Salaam, Tanzania, Kampala, Uganda, Nairobi, Kenya, and also for neighboring Maputo, Mozambique. The stand-out result is the relatively high collection coverage achieved, in Maputo with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 39 publications
0
47
0
7
Order By: Relevance
“…During the COVID-19 pandemic, infectious municipal SW and WW treatment is a critical issue worldwide to tackle the exponential increase of infectious waste generation during this period. This is even true for African developing and underdeveloped countries where the municipal WM is generally more economic-oriented and practiced in an unsustainable way (Idowu et al 2019;Kabera et al 2019). Recently, many government task forces have been formed in African countries to develop guidelines and operating procedures for managing infectious waste from COVID-19 in risk zones.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, infectious municipal SW and WW treatment is a critical issue worldwide to tackle the exponential increase of infectious waste generation during this period. This is even true for African developing and underdeveloped countries where the municipal WM is generally more economic-oriented and practiced in an unsustainable way (Idowu et al 2019;Kabera et al 2019). Recently, many government task forces have been formed in African countries to develop guidelines and operating procedures for managing infectious waste from COVID-19 in risk zones.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular ways to eliminate waste in Africa involve using open dump sites. In fact, according to [4], only Kampala (Uganda) has an engineered disposal site. The ongoing disposal of MSW in poorly engineered "dump sites" on the outskirts of Al-Bayda (Libya) is unsustainable and will not meet the demands of the growing population and increasing urbanization [5].…”
Section: Introductionmentioning
confidence: 99%
“…From the selected manuscripts, Kabera et al (2019) carried out a benchmark performance of combined solid waste management and recycling systems in major cities of East Africa. The authors identified the major strengths of the individual waste management concepts, as well as the common bottlenecks that prevent a more efficient implementation of the designed management concepts.…”
mentioning
confidence: 99%